2022
DOI: 10.7759/cureus.24366
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter: A Rare Cause of Rapid Development of Cavitary Lung Lesion Following COVID-19 Infection

Abstract: Cavitary lesions of the lungs are a very frequent picture found in clinical practices resulting from a wide range of pathological processes with variable duration of formation depending on infectious pathogens. Common organisms causing cavitary lesions are Staphylococcus aureus , Klebsiella pneumoniae , Streptococcus pneumoniae , Haemophilus influenzae , typical and atypical Mycobacterium , and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Although significant differences may be seen on CT scans from COVID-19 patients, typical characteristic radiographic features include multifocal and bilateral ground-glass opacities in a predominantly peripheral distribution [ 1 ]. CT findings of pleural effusion, pericardial effusion, and pulmonary cavitation are uncommon and should prompt further investigation in these patients given the increased rates of morbidity and mortality seen with viral-bacterial coinfections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although significant differences may be seen on CT scans from COVID-19 patients, typical characteristic radiographic features include multifocal and bilateral ground-glass opacities in a predominantly peripheral distribution [ 1 ]. CT findings of pleural effusion, pericardial effusion, and pulmonary cavitation are uncommon and should prompt further investigation in these patients given the increased rates of morbidity and mortality seen with viral-bacterial coinfections.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) involves multiple organ systems, mainly lungs [ 1 ]. Secondary bacterial infections are very common in post-viral infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several trials highlighted the importance of MDR Acinetobacter pneumonia (AP), reporting mortality rates near to 90%, especially in patients who required mechanical ventilation [10]. Typically, these bacteria will cause VAP, especially in critically ill patients; recent studies have shown that approximately 1-28% of COVID-19 patients with the active disease on ventilators will subsequently develop a superimposed Ab infection while on the ventilator [11]. Furthermore, Carbapenem-resistant Ab infections in COVID-19-positive patients admitted to the ICU were more frequent compared to those that were COVID-19 negative [12].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, in the literature, there have been reported some case report and series, but there is no previous report which focuses on the imaging findings of AP [11,[18][19][20]. The aim of this retrospective study was to describe the imaging features on CXRs and CT scans in hospitalized patients with MDR AP, which can help to suspect an infection.…”
Section: Introductionmentioning
confidence: 99%